Systematic Review: The Use of FTIR Spectroscopy for Pharmaceutical Analysis, Herbal Medicine, and the Identification of Chemical Compounds - Mita Rasyida; Muhammad Adi Utama; Faneshia Nabil Ayushita; Aulia Jihan Kamila; Adelliana Putri Puspitasari; Lubna Nurul Mumtazah; Clarissa Zuha Swari (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Fourier Transform Infrared Spectroscopy (FTIR) is a vibrational spectroscopic technique widely used to identify functional groups and characterize molecular structures based on infrared absorption patterns. This literature review aims to evaluate the application of FTIR in pharmaceutical and herbal analysis, particularly for identifying active pharmaceutical ingredients, detecting adulterants, characterizing secondary metabolites, and determining drug content in pharmaceutical preparations. Method: This review employed a systematic literature review approach, including database searching, article screening based on inclusion and exclusion criteria, and narrative synthesis of qualitative and quantitative findings from 21 selected studies related to FTIR applications in pharmaceutical and herbal products. Result: The reviewed studies demonstrated that FTIR provides rapid, nondestructive, and environmentally friendly analysis with minimal sample preparation. FTIR showed excellent linearity, accuracy, and precision for quantitative analysis, with results comparable to standard analytical methods. In addition, FTIR was effective in detecting adulterants such as paracetamol and dexamethasone in herbal medicines through characteristic fingerprint peaks. The technique also showed broad applicability for routine quality control in pharmaceuticals and herbal products. Conclusion: FTIR is a versatile, rapid, and green analytical technique suitable for screening, qualitative identification, and simple quantitative analysis in pharmaceutical and herbal products. Although FTIR has limitations, including lower sensitivity compared to chromatographic methods and signal overlap in complex matrices, it remains a reliable and practical tool for routine quality control applications.